ELEMEN KOTA ISLAMI DALAM TATA RUANG KOTA BOGOR - Raisatun Nisaa Firdausiyah Abdur Rouf Sam (Mozaic : Islam Nusantara, 2022)
The Islamic city was originally a city built by the Prophet Muhammad Shollahu 'Alaihiwassalam with several considerations of ideological concepts that carried positive values ​​in Islam. An Islamic city is a city founded by Muslims for some time (Islamic civilization) or a downtown area that has certain elements identified as the main mosque, palace, market, cemetery, fort, Islamic law and various ethnic communities. The Islamic city is formed on various vertical and horizontal principles of life to achieve an Islamic identity. The city of Bogor is a city formed by the colonial government and is not the territory of the former Islamic kingdom. However, in its development the city of Bogor has elements of an Islamic city. Based on the results of the study, the spatial layout of Bogor City has 11 elements of an Islamic City. The non-physical elements discussed are elements of the Islamic City which include social and cultural elements, as well as government and policies in the City of Bogor. The physical elements of the Islamic City observed include the main road network, supporting road network, masjid jami, musalla (smaller prayer rooms/mosques), suqs (markets), citadel/ksar (royal palaces/local rulers), sur (walls), public squares, Islamic schools, settlements, turba and maqraba (private and public cemeteries), and qasaba (fortresses). Based on the level of tendency to develop, there are 11 elements that are getting stronger or their existence is increasing in the Islamic City element from the previous condition. There are 5 elements of the city that have undergone many changes to the building or facility. There are 9 elements of the city that have a positive or good impact on development time.